2004
DOI: 10.1183/09031936.04.00047503
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of narrowing in normal and asthmatic airways measured by HRCT

Abstract: Asthmatic airway narrowing is heterogeneous and contributes to airway hyperresponsiveness. The present study compared heterogeneity of narrowing during methacholine challenge in asthmatics and normal subjects using high-resolution computed tomography (HRCT).The current authors defined heterogeneity as variability in narrowing greater than the repeatability of measurement. Airways of v2 mm diameter were compared with larger airways from baseline and postmethacholine HRCT of the right lower lung in 13 normals (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 28 publications
3
103
0
1
Order By: Relevance
“…GOLDIN et al [75] reported greater decreases in FEV1 and in airway lumen area in small airways after inhalation of methacholine in asthmatic as opposed to normal subjects. KING et al [27] have recently shown that airway narrowing is heterogeneous in the large airways of asthmatics, and that this heterogeneity is larger than in control subjects.…”
Section: Airway Imaging In Asthma Airway Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…GOLDIN et al [75] reported greater decreases in FEV1 and in airway lumen area in small airways after inhalation of methacholine in asthmatic as opposed to normal subjects. KING et al [27] have recently shown that airway narrowing is heterogeneous in the large airways of asthmatics, and that this heterogeneity is larger than in control subjects.…”
Section: Airway Imaging In Asthma Airway Dimensionsmentioning
confidence: 99%
“…KING et al [27] measured heterogeneity in airway narrowing by comparing the variation within a scan to that between scans. However, this study did not address the issue of heterogeneity in baseline airway dimensions, which is important to estimate before the quantitative assessment of airway dimensions is established as an outcome measure in clinical studies.…”
Section: Quantitative Assessment Of Smaller Airwaysmentioning
confidence: 99%
“…According to current literature, radiographic measurements of bronchi that are smaller than segmental ones are problematic [23]. Size determination (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Following MCh challenge, Brown et al [30] reported airway reductions with standard error values sufficient to suggest that for airways >7 mm at baseline, dilation instead of constriction after bronchoprovocation occurred in slightly less than half of the airways in healthy subjects, and slightly less than 16% of the airways in asthmatic subjects. Likewise, Bland-Altman plots put forth by King et al [29] show 18.5% of measured healthy airways and 20.8% of measured asthmatic airways dilated following MCh challenge. Both studies include data from airways smaller than what we can measure using HP 3 He MRI.…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%
“…Instead of grouping imaged airways by size and confined to particular locations [29][30][31][32], this study tracked individual central airway calibers. HP 3 He MRI could be established as a viable alternative for quantitatively assessing bronchial response if it could be demonstrated that it measures airway diameter changes comparable to those derived from MDCT data.…”
Section: Introductionmentioning
confidence: 99%